Efeito do consumo agudo de erva mate sobre o rendimento fisíco em esteira ergométrica e indicadores metabólicos da exaustão em jogadores profissionais de futebol - Oliveira, Erick Prado de [UNESP] (2014)
Background: Yerba mate tea (Ilex Paraguariensis) is an herbal tea beverage consumed mainly in South America that presents components with antioxidant, antinflammatory, and possible ergogenic properties. It is known that exercise increases oxidative stress and muscle damage, and then mate tea intake could show beneficial effects. Purpose: To evaluate the effect of acute intake of yerba mate on blood markers of oxidative stress and muscle damage in female soccer players exposed to exhaustive exercise. Methods: 15 female soccer players (22.1 ± 4.2 years old) were studied randomized with either 5g of soluble yerba mate (400 ml) or 400 ml of water cross-overly with 7 days of washout. Both liquids were given after an overnight fasting and before 60 minutes of a treadmill incremental test up to exhaustion. All subjects were fed with 30g of maltodextrin 30 minutes before the beginning of the test. From the treadmill performance of the drinking-water players it was evaluated all the individuals and also was created the sub groups of Higher Run Time (HRT, n=8) and the others (WRT, n=7). Blood samples were collected before and immediately post-exercise and assayed for markers of tissue integrity (enzymes CK, AST and ALT), antioxidants (TAP and uric acid), oxidants (MDA) and anaerobiosis (lactate). It was used repeated-measures ANOVA to compare the variables in basal, pre and post-exercise; and t-test dependent to compare the delta (final-initial) values ( ) and time of treadmill run between groups, for p<0.05. Results: In all the individuals it was noted higher lactate and lower ALT levels after the exercise in mate group. The yerba mate tea group showed longer treadmill run along with higher increase of lactate and uric acid than the water group in the WRT sub group. In HRT it was observed no increase in AST and lower ALT levels in mate tea group. Conclusion: Yerba mate intake by female soccer players increased tolerance to exhaustive exercise ...